Fatal Systemic Toxoplasma gondii Infection in a Red Squirrel (Sciurus vulgaris), a Swinhoe's Striped Squirrel (Tamiops swinhoei) and a New World Porcupine (Erethizontidae sp.). Issue 2 (February 2016) - Fayyad, A.; Kummerfeld, M.; Davina, I.; Wohlsein, P.; Beineke, A.; Baumgärtner, W.; Puff, C.
Summary: Toxoplasmosis is a parasitic disease that affects man and animals worldwide. The primary hosts and major reservoir for Toxoplasma gondii are felids and the intermediate hosts are most warm-blooded animals including man. This report describes fatal toxoplasmosis in three different rodent species in Germany: a female red squirrel ( Sciurus vulgaris ) and a male Swinhoe's striped squirrel ( Tamiops swinhoei ), both kept as pets, and a female New World porcupine ( Erethizontidae sp.) from a zoo. All three animals had multifocal necrotizing hepatitis. Additional findings included lymphohistiocytic and necrotizing myocarditis in the New World porcupine and the Swinhoe's striped squirrel, lymphohistiocytic encephalomyelitis in the New World porcupine and suppurative lymphadenitis in the red squirrel. Numerous tachyzoites were identified associated with the lesions. The diagnosis was confirmed by Toxoplasma. gondii immunohistochemistry and electron microscopy. This is the first report of toxoplasmosis in a New World porcupine and a Swinhoe's striped squirrel.